An Educational Gaze From the International Union of Soil Sciences - Reyes-Sánchez, Laura B. (Spanish Journal of Soil Science, 2024)
A lack of fertile soil is already a serious problem due to its role in access to sufficient food and water, but more serious are the social situations that its deficit engenders: loss of food safety and public health, poverty, displacement, inequality, violence, and injustice as a result of famine. The loss and degradation of the soil resource means the loss of all terrestrial flora, and with it, that of the fauna that it feeds. It also means a terrible loss of biodiversity at the planetary level, a serious destruction of the food chain of which we are a part, as well as the reduction of its capacities of available water reserve and C capture to lessen climate change in the long term and with immediate effects. In this context, the protection of the soil resource and an interdisciplinary and innovative education and practice of sciences to raise citizens’ awareness of the importance of its preservation—with all the sciences collaborating as a team in a mediatized world—are keys to achieving the Sustainable Development Goals, and therefore, are the long-term goals and prioritized objectives of the International Decade of Soils of the IUSS, and they form the basis of its educational project.